2017
DOI: 10.1016/j.pmedr.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in lipid testing among children and adolescents: A population based study

Abstract: Unfavorable lipid levels during childhood are associated with subsequent development of atherosclerotic cardiovascular disease. The American Academy of Pediatrics and National Heart, Lung and Blood Institute in 2011 recommended universal lipid screening for children between ages 9–11 years and between ages 17–21 years. The objective of the study was to determine temporal trends in lipid testing among children and young adults in a mid-western population. The Rochester Epidemiology Project database was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…11 In the United States, although some studies have shown lipid screening rates of around 20%, 16,17 other analyses have identi fied lower rates (2%-7%) in otherwise healthy children. [18][19][20][21] Although we were unable to determine the reason for lipid assessment in the present study, it is reasonable to assume that a substantial proportion of assessments were performed as part of a selective screening approach related to the presence of other cardiovascular risk factors or the diagnosis of pre mature cardiovascular disease in family members. 14 Support ing this, the frequency of initial lipid assessment increased gradually with age, from 0.1% among 2yearold children to 4.8% among 17yearold adolescents, suggesting that assess ments may have been performed owing to the presence of other risk factors that accumulated with time.…”
Section: No Of Lipid Assessmentsmentioning
confidence: 83%
See 1 more Smart Citation
“…11 In the United States, although some studies have shown lipid screening rates of around 20%, 16,17 other analyses have identi fied lower rates (2%-7%) in otherwise healthy children. [18][19][20][21] Although we were unable to determine the reason for lipid assessment in the present study, it is reasonable to assume that a substantial proportion of assessments were performed as part of a selective screening approach related to the presence of other cardiovascular risk factors or the diagnosis of pre mature cardiovascular disease in family members. 14 Support ing this, the frequency of initial lipid assessment increased gradually with age, from 0.1% among 2yearold children to 4.8% among 17yearold adolescents, suggesting that assess ments may have been performed owing to the presence of other risk factors that accumulated with time.…”
Section: No Of Lipid Assessmentsmentioning
confidence: 83%
“…Previous work has similarly shown that limited access to care impedes routine health assessments, including pediatric lipid assess ments. 17,21 Strategies are thus needed to improve rates of lipid screening in vulnerable communities with reduced access to primary care. 22 We leveraged an overlap of ages between the 2 cohorts (9 and 10yearold children) to evaluate changes in lipid assess ment practices between the cohort periods (2012-2014 for those from the older cohort v. 2019-2021 for those from the younger cohort).…”
Section: No Of Lipid Assessmentsmentioning
confidence: 99%
“…Despite the high frequency of dyslipidemia in children and universal screening guidelines, screening rates are still very low [41][42][43]. Therefore, the true prevalence of dyslipidemia is likely underestimated.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…Despite the availability of well tolerated and efficacious treatment options, children with hypercholesterolemia are frequently underdiagnosed, untreated or undertreated. Although NHLBI guidelines recommend universal screening, there guidelines are not being universally implemented [114][115][116][117]. Efforts to increase awareness among generalists and to remove barriers to such care will be essential for implementation.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%